Virtual reality pain control during burn wound debridement in the hydrotank - Hoffman, Hunter G; Patterson, David R; Seibel, Eric; Soltani, Maryam; Jewett-Leahy, Laura; Sharar, Sam R (The Clinical journal of pain, 2008)
Most burn-injured patients rate their pain during burn wound debridement as severe to excruciating. We explored the adjunctive use of water-friendly, immersive virtual reality (VR) to distract patients from their pain during burn wound debridement in the hydrotherapy tank (hydrotank). This study was conducted on inpatients at a major regional burn center. Eleven hospitalized inpatients ages 9 to 40 years (mean age, 27 y) had their burn wounds debrided and dressed while partially submerged in the hydrotank. Although a nurse debrided the burn wound, each patient spent 3 minutes of wound care with no distraction and 3 minutes of wound care in VR during a single wound care session (within-subject condition order randomized). Three 0 to 10 graphic rating scale pain scores (worst pain, time spent thinking about pain, and pain unpleasantness) for each of the 2 treatment conditions served as the primary dependent variables. Patients reported significantly less pain when distracted with VR [eg, "worst pain" ratings during wound care dropped from "severe" (7.6) to "moderate" (5.1)]. The 6 patients who reported the strongest illusion of "going inside" the virtual world reported the greatest analgesic effect of VR on worst pain ratings, dropping from severe pain (7.2) in the no VR condition to mild pain (3.7) during VR. Results provide the first available evidence from a controlled study that immersive VR can be an effective nonpharmacologic pain reduction technique for burn patients experiencing severe to excruciating pain during wound care. The potential applications of VR analgesia to other painful procedures (eg, movement or exercise therapy) and other pain populations are discussed.